2019
DOI: 10.1007/s40618-019-01026-5
|View full text |Cite
|
Sign up to set email alerts
|

Changes in left ventricular repolarization after short-term testosterone replacement therapy in hypogonadal males

Abstract: Background and aim Evidences suggest that androgen deficiency is associated with sudden cardiac death (SCD). Our purpose was to analyse some electrocardiographic (ECG) markers of repolarization phase in hypogonadal patients either at baseline or after testosterone replacement therapy (TRT). Patients and Methods Baseline and after 6 months of testosterone replacement therapy, 14 hypogonadal patients and 10 age-matched controls underwent a short-term ECG recordings at res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 62 publications
(85 reference statements)
3
19
0
Order By: Relevance
“…Taking into account the findings of Piccirillo et al [35], who studied 14 hypogonadal patients and 10 age-matched controls and found no difference in Tpe, we can assume that the significant prolongation of Tpe and Tpe/QT in our study group A reflects the effect of the combination of degarelix with enzalutamide, not of the hypogonadism itself.…”
Section: Discussionsupporting
confidence: 63%
“…Taking into account the findings of Piccirillo et al [35], who studied 14 hypogonadal patients and 10 age-matched controls and found no difference in Tpe, we can assume that the significant prolongation of Tpe and Tpe/QT in our study group A reflects the effect of the combination of degarelix with enzalutamide, not of the hypogonadism itself.…”
Section: Discussionsupporting
confidence: 63%
“…To calculate repolarization variables a template method has been used 17 . We designed and produced a software for data acquisition, storage, and analysis with the LabView program (National Instruments), which applies the technical recommendation of consensus guidance endorsed by European Heart Rhythm Association jointly with the European Society of Cardiology Working Group on cardiac cellular electrophysiology, as described in detail in previous papers 1,2,8‐13,18,19 …”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we measured the following intervals from the respective time series in ECG recordings: RR, QTe, QTp, and Te; QTe was obtained measuring the interval from the Q‐wave to the T‐wave end; QTp was obtained measuring the interval from the Q‐wave to the T‐wave peak; Te was obtained from T peak to end of T wave (Figures 1 and 2). 7‐13 To identify the repolarization intervals, we used a software originally proposed by Berger 17 and validated in other subsequently studies 1 . We therefore calculated mean, variance, and standard deviation (QTe SD , QTp SD , and Te SD ) values for each of these repolarization phase intervals 1 ; consequently, we calculated the QTe, QTp, and Te variability index (QTeVI, QTpVI, and TeVI) 1,17 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations